2020
DOI: 10.1038/s41598-020-64036-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soil fertility and potato crop nutrient status in central and eastern highlands of Kenya

Abstract: Inherent low soil fertility remains a hindrance to potato production in Kenya and continues to pose a threat to food security. A study was conducted in Nyandarua and Meru counties to assess the soil fertility status in smallholder potato farms. Soil and plant tissue samples were collected and analysed for selected nutrients (pH, OC, N, P, K, S, Ca, Mg, Zn, B and Cu) from 198 farms. Critical nutrient levels were used to assess the sufficiency levels of nutrients for potato growth. Soils in the sampled farms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…Another possible explanation can be a poor nutrient status in the soil of Kenya and India ( Sharma et al, 2009 ; Mugo et al, 2020 ; Stewart et al, 2020 ), which represent our high-VPD agroecosystems. It has been shown that the landrace maize Sierra Mixe, originally from a nitrogen-depleted region in Mexico, gets a considerable amount of its nitrogen demand through biological nitrogen fixation by diazotrophs abundant in mucilage produced by its huge nodal roots ( Van Deynze et al, 2018 ; Amicucci et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation can be a poor nutrient status in the soil of Kenya and India ( Sharma et al, 2009 ; Mugo et al, 2020 ; Stewart et al, 2020 ), which represent our high-VPD agroecosystems. It has been shown that the landrace maize Sierra Mixe, originally from a nitrogen-depleted region in Mexico, gets a considerable amount of its nitrogen demand through biological nitrogen fixation by diazotrophs abundant in mucilage produced by its huge nodal roots ( Van Deynze et al, 2018 ; Amicucci et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heavy clay soils are unfavorable for potatoes (Johansen et al, 2015). On such soils, especially in wet years, there is a risk of yield loss due to the rapid spread of plant diseases (Liao et al, 2016;Shi et al, 2019;Mugo et al, 2020). Territorial units, where the rate of increase is higher, are in accordance with the predominance of light soils (Figure 1, Figure 5).…”
Section: Resultsmentioning
confidence: 97%
“…Potatoes require soil organic matter for nutrient supply, improved nutrient use efficiency, and soil water conservation. The use of manure in potato production is common in East Africa and has been confirmed by Tadesse et al (2017) and Mugo et al (2020). The benefits of using manure/compost include nutrient source, improvement of soil pH, increased soil organic matter, soil organic carbon, and crop yields (Linus et al, 2004;Muthoni and Kabira, 2011;Otieno et al, 2018).…”
Section: Potatoes Tuber Response To Manure/compost Applicationmentioning
confidence: 99%